Smart Shoe Gadget for Visually Impaired People - Alotaibi, Hassan; Javed, Ravish; Alghannam, M. Saleh; Saqer, M. Fahad; AlQahtani, Mahdi (European Journal of Applied Sciences, 2022)
Human beings have a variety of senses such as hearing, sight, smell, taste, and touch which enable them to complete their desired tasks as per the situation without any assistance. The most vital among all the senses is the sense of sight as it is the primary input for the brain but such conditions have never been the same for visually impaired individuals. With the use of technology, we can develop a smart prototype that can help and serve visually impaired people. Our aim is to design a smart shoe device to help visually impaired people to be independent in their daily lives without depending on others. To make the device lightweight, easy to use, cheap in price, and portable. We have used limited components such as Arduino Uno®, Power Supply, Ultrasonic Sensor, Water Sensor, Switch, Buzzer, and Vibrator. Ultrasonic sensor and water sensor were connected to a Vibrator (VM 0610 A 3.0) and a Buzzer (CMI-9605IC-0580T), respectively. The range of ultrasonic sensor was set to be used for 1 meter and 2 meters distance ranges that can be controlled via a switch. Our proposed concept of smart shoe prototype is to assist visually impaired people while walking indoor and outdoor that can help them walk independently and they can get alerts for objects and wet surfaces coming their way. Thus they can avoid mishap by using our prototype.